Coded cooperation: generalised outage analysis. Issue 6 (1st April 2014) - Sharma, Prabhat Kumar; Garg, Parul
Abstract : In this study, the authors derive the exact closed‐form expression of the outage probability for coded cooperation using power‐based approach. They consider a generalised system model with n relays ( n > 1) over Nakagami‐ m fading channels. They also obtain the optimal number of relays for the given outage performance. Furthermore, they find analytically the critical cooperation ratio at which the total outage probability is minimum.